Resistance to thyroid hormone due to a novel mutation in the thyroid beta receptor (THRβ) gene coexisting with autoimmune thyroid disease—A case report - Skowrońska-Jóźwiak, Elżbieta; Gach, Agnieszka; Cyniak-Magierska, Anna; Nykel, Anna; Jurkowska, Monika; Lewiński, Andrzej (Frontiers in Genetics, 2023)
Resistance to thyroid hormone (RTH) is a syndrome characterized by impaired responsiveness of target tissues to thyroid hormones. The relationship between RTHβ and thyroid autoimmunity has been under research. In this study, we demonstrate a case report of a woman with a novel mutation in THRβ gene coexisting with autoimmune thyroid disease (AITD). The 36-year-old woman has been treated since childhood for a thyroid disease. Based on high levels of thyroid hormones (THs) and elevated concentrations of thyroperoxidase and thyroglobulin antibodies (TPOAb and TgAb, respectively), she received unnecessary long-term treatment with methimazole and finally underwent subtotal thyroidectomy. After the surgery, her TSH level remained significantly elevated, despite the treatment with 150 + 15 µg of thyroxine and triiodothyronine. A sequence analysis of the THRβ gene revealed a novel dinucleotide substitution affecting codon 453, resulting in the replacement of the normal proline with an asparagine (c.1357_1358delinsAA, p.(Pro453Asn)). The mutation has not been described in the literature yet; however, THRβ codon 453 represents a mutational hot spot, frequently altered in the TH receptor ß gene. After establishing the diagnosis of RTH, the patient was treated with 300 µg of thyroxine, which showed clinical improvement and normalization of TSH. The coexistence of RTHβ and AITD may additionally impede establishment of a proper diagnosis, leading to unnecessary therapy and delayed correct treatment. The presented case encourages a closer cooperation between clinical endocrinologists and geneticists.